The emerging role of TET enzymes in the immune microenvironment at the maternal-fetal interface during decidualization and early pregnancy - Jin, Mengmeng; Ji, Jianxiong; Chen, Xi; Zhou, Ying; Wang, Dimin; Liu, Aixia (Frontiers in Immunology, 2023)
Dysregulated immune microenvironment at the maternal-fetal interface in early pregnancy may lead to early pregnancy loss, fetal growth restriction, and preeclampsia. However, major questions about how epigenetic modifications regulate immunemicroenvironment during decidualization process and embryo implantation remain unanswered. DNA methylation, the main epigenetic mechanism involved in endometrial cycle, is crucial for specific transcriptional networks associated with endometrial stromal cells (ESCs) proliferation, hormone response, decidualization, and embryo implantation. TET enzymes, responsible for catalyzing the conversion of 5-methylcytosine (5mC) to 5-hydroxymethylcyosine (5hmC), 5-formylytosine (5fC), and 5-carboxylcyosine (5caC) to achieve DNA demethylation process, appear to have critical roles in decidualization and embryo implantation. Here, we provide comprehensive view of their structural similarities and common mechanism of regulation in microenvironment at maternal-fetal interface during decidualization and early pregnancy. We also discuss their physiological role in decidual immune microenvironment. Finally, we propose a key hypothesis regarding TET enzymes at maternal-fetal interface between decidual immune cells and endometrial stromal cells. Future work is needed to elucidate their functional role and examine therapeutic strategies targeting these enzymes in pregnancy related diseases preclinical models, which would be of great value for future implications in disease diagnosis or treatment.